Assessment of Hematological Profile of Pregnant Women - Pujitha Devi Suraneni; Sujatha (Asian Journal of Medical Research, 2020)
Background: To assess hematological profile of pregnant women. Subjects and Methods: One hundred fifty- six women in age ranged 20-40 years were selected. Group I were pregnant women and group II were control. Determination of packed cell volume (PCV), total white cell count (WBC), differential counts, erythrocyte sedimentation rate (ESR) was performed. Results: The mean WBC (X109/L) was 7.1 in group I and 4.3 in group II, neutrophil was 53.2% in group I and 43.6% in group II, eosinophil was10.4% in group I and 6.5% in group II, basophil was 1.21% in group I and 1.32% in group II, monocyte 1.42% in group I and 4.51% in group II, lymphocyte was 35.4% in group I and 45.7% in group II, PCV 31.2% in group I and 38.4% in group II and ESR was 28.4 mm/hr in group I and 11.3 mm/hr in group II respectively. The mean parameters recorded at trimester 1, trimester 2 and trimester 3 showed values of WBC (X109/L) as 6.7, 7.4 and 8.1, neutrophil (%) as 54.2, 46.6 and 55.7, eosinophil (%) as 10.4, 9.5 and 10.6, basophil (%) as 1.29, 1.0 and 1.0, monocyte (%) as 1.42, 0.76 and 1.35, lymphocyte (%) as 34.4, 42.7 and 31.8, PCV (%) as 30.2, 32.4 and 31.6 and ESR (mm/hr) as 34.4, 31.3 and 27.6 respectively. The difference was on- significant (P> 0.05). Conclusion: There was alteration in hematological value in pregnant women. A careful examination of these indices is of paramount importance at various trimesters of pregnancy on order to avoid complications.